Greater socioenvironmental risk factors and higher chronic pain stage are associated with thinner bilateral temporal lobes - Lisa H. Antoine; Jared J. Tanner; Angela M. Mickle; Cesar E. Gonzalez; Daniel A. Kusko; Kristen Allen Watts; Deanna D. Rumble; Taylor L. Buchanan; Andrew M. Sims; Roland Staud; Song Lai; Hrishikesh Deshpande; et al. (Brain and Behavior, 2023)
Abstract Introduction: Previous research indicates ethnic/race group differences in pain and neurodegenerative diseases. Accounting for socioenvironmental factors reduces ethnic/race group differences in clinical and experimental pain. In the current study sample, we previously reported that in individuals with knee pain, ethnic/race group differences were observed in bilateral temporal lobe thickness, areas of the brain associated with risk for Alzheimer's disease, and related dementias. The purpose of the study was to determine if socioenvironmental factors reduce or account for previously observed ethnic/race group differences and explore if a combined effect of socioenvironmental risk and chronic pain severity on temporal lobe cortices is evident. Methods: Consistent with the prior study, the sample was comprised of 147 adults (95 women, 52 men), 45–85 years of age, who self‐identified as non‐Hispanic Black (n = 72) and non‐Hispanic White (n = 75), with knee pain with/at risk for osteoarthritis. Measures included demographics, health history, pain questionnaires, cognitive screening, body mass index, individual‐ and community‐level socioenvironmental factors (education, income, household size, marital and insurance status, and area deprivation index), and brain imaging. We computed a summative socioenvironmental risk index. Results: Regression analyses showed that with the inclusion of socioenvironmental factors, the model was significant (p < .001), and sociodemographic (ethnic/race) group differences were not significant (p = .118). Additionally, findings revealed an additive stress load pattern indicating thinner temporal lobe cortices with greater socioenvironmental risk and chronic pain severity (p = .048). Implications: Although individual socioenvironmental factors were not independent predictors, when collectively combined in models, ethnic/race group differences in bilateral temporal lobe structures were not replicated. Further, combined socioenvironmental risk factors and higher chronic pain severity were associated with thinner bilateral temporal lobes.